2016
DOI: 10.1111/echo.13432
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the brachial artery endothelial function in chronic alcohol consumption among males by high‐frequency ultrasonography

Abstract: Chronic moderate-to-heavy alcohol consumption caused endothelial dysfunction, even damaging vascular smooth muscle cells in cases of heavy alcohol consumption, while abstinence and chronic mild alcoholics caused no effect on endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…Two studies had findings confounded by either smoking (Papamichael et al, 2004) or olive oil consumption (Karatzi et al, 2008), and one study only reported alcohol use over the past 30 days (yes/no) with no information on the amount of alcohol consumed (Hill et al, 2020). For these reasons, we excluded these 13 studies, and therefore, 31 studies met inclusion criteria and were included in the research synthesis (Agewall et al, 2000; Andrade et al, 2009; Bau et al, 2005; Boban et al, 2006; van Bussel et al, 2018; Coimbra et al, 2005; Cuevas et al, 2000; Djousse et al, 1999; Di Gennaro et al, 2007, 2012; Goslawski et al, 2013; Hampton et al, 2010; Hashimoto et al, 2001; Hijmering et al, 2007; Huang et al, 2010; Karatzi et al, 2004, 2013; Luo et al, 2017; Maiorano et al, 1999; Muggeridge et al, 2019; Oda et al, 2017, 2020; Schaller et al, 2010; Spaak et al, 2008; Suzuki et al, 2009; Tanaka et al, 2016; Teragawa et al, 2002; Vlachopoulos et al, 2003; Whelan et al, 2004; Zilkens et al, 2003, 2005). Among these studies, only six studies were published within the past 5 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies had findings confounded by either smoking (Papamichael et al, 2004) or olive oil consumption (Karatzi et al, 2008), and one study only reported alcohol use over the past 30 days (yes/no) with no information on the amount of alcohol consumed (Hill et al, 2020). For these reasons, we excluded these 13 studies, and therefore, 31 studies met inclusion criteria and were included in the research synthesis (Agewall et al, 2000; Andrade et al, 2009; Bau et al, 2005; Boban et al, 2006; van Bussel et al, 2018; Coimbra et al, 2005; Cuevas et al, 2000; Djousse et al, 1999; Di Gennaro et al, 2007, 2012; Goslawski et al, 2013; Hampton et al, 2010; Hashimoto et al, 2001; Hijmering et al, 2007; Huang et al, 2010; Karatzi et al, 2004, 2013; Luo et al, 2017; Maiorano et al, 1999; Muggeridge et al, 2019; Oda et al, 2017, 2020; Schaller et al, 2010; Spaak et al, 2008; Suzuki et al, 2009; Tanaka et al, 2016; Teragawa et al, 2002; Vlachopoulos et al, 2003; Whelan et al, 2004; Zilkens et al, 2003, 2005). Among these studies, only six studies were published within the past 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…3.5.3 | Long-term effect of alcohol consumption on FMD As noted above, the majority of studies including individuals with a history of lifetime, chronic or repeated alcohol consumption, included a control or abstinent/nondrinker group (Table 3). Compared to controls, there was a decrease in FMD reported in nearly all the studies that enrolled individuals with a history of chronic alcoholism (≥6 drinks/ day for ≥2 years; with or without abstinence; Di Gennaro et al, 2007Gennaro et al, , 2012Luo et al, 2017;Maiorano et al, 1999), with a history of repeated binge drinking (Goslawski et al, 2013), with a past year history of heavy drinking (>280 g/ week; Oda et al, 2017Oda et al, , 2020, and with a lifetime history at a heavy drinking (≥46 g/day; Tanaka et al, 2016). On the other hand, while one study did not find the association of alcohol consumption over the past year with FMD (van Bussel et al, 2018), another study reported that a lifetime of alcohol consumption (1 drink/month to 2 drinks/day) was associated with an increased odds ratio for improved FMD (Suzuki et al, 2009).…”
Section: Studies Examining the Effect Of Longterm Alcohol Consumptionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, in south of China, although a traditional dinner party generally tends to consume all kinds of alcoholic beverage and plenty of meat, no previous data revealed the effect of alcohol and meat on RHI-measured micro-vascular ED. However, several studies that used the FMD index to evaluate the alcohol effect were controversial: chronic moderate to heavy alcohol consumption caused macro-vascular endothelial dysfunction in Asian men 34,35 , and even FMD was signi cantly smaller in light alcohol drinkers 36 . Conversely, the consumption of moderate and high alcoholic beverages was independently associated with better FMD, when compared to no alcohol consumption 37,38 , especially when consuming red wine 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In morphological studies, ultrasound has been employed to image the tunica intima and tunica media of blood vessels and diagnose plaques, thrombosis and other vascular diseases ( 7 , 8 ). In functional studies, ultrasound has been used to examine vascular endothelial function ( 9 ). Due to the increasing understanding of disease theories, clinical techniques are being updated and improved synchronously.…”
Section: Ultrasound In Carotid Atherosclerosismentioning
confidence: 99%